Developing a Conceptual Model of Customer Loyalty in the Mass Housing Industry: The Case of Housing Investment Group Company - Karimi Alavijeh, M. R.; Jamshidi Majd, M.; Aslani Afrashteh, A. (Indian Journal of Marketing, 2019)
The aim of this research was to develop a conceptual model of customer loyalty in the mass housing investment companies in Iran. The data for this research were gathered at the end of 2016 and the analysis was carried using an exploratory (qualitative-quantitative) approach. At first, the primary conceptual model was developed using theoretical foundations and literature review as well as using data from our initial exploratory study of building industry experts. Then in the qualitative section, the final model and the final questionnaire (for the quantitative stage) were indigenized by using content analysis and semi-structured interviews with 11 professional and university experts selected by judgment. In the quantitative stage, the final model was tested using structural equation modeling with 158 loyal customers of the Housing Investment Company, who were selected by using stratified random sampling method from all over the country. The findings of this research showed that factors of quality, economics, and customer relationship management affected satisfaction. In addition, the effects of satisfaction on trust, commitment to loyalty, and loyalty to word-of-mouth advertising were accepted.